COVID-19 AND ITS IMPACT ON UNIVERSITY EDUCATION IN PERU. A RESEARCH ON STUDENTS OF THE FIRST TWO CYCLES OF A PRIVATE UNIVERSITY OF LIMA - YALLE-QUINCHO, Omar (2024)
The objective of this research was to know the impact of the COVID-19 pandemic at the Ricardo Palma University. It is a mixed methodology study, of an exploratory-descriptive type. A survey guide with 2 thematic sections of 7 items was applied to 110 respondents, its application being as follows; 78 virtual and 32 in-person, in the first cycles of the Basic Studies Program of the Ricardo Palma University, between the 2021-2, 2022.1 and 2022-2 semesters of both sexes between 16 and 25 years of age. The results indicate thatCOVID-19 regularly affected the economic and family aspects, health due to the contagion of the disease, and mental health. The measures adopted by the University during the context have been as expected and have been taken positively, both from the institutional side and from the teachers and students. Likewise, the response of students to teaching-learning has been as expected, in the development of virtual education.